Linear Feedforward Control Of Two-Level Quantum System By Modulated External Field - Borisenok, Sergey; Saifullah (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2011)
We propose a model of feedforward (open-loop) optical control of two-level atom in the linear form. This model allows to express the general form of solution for the atomic level populations via the arbitrary shapes of the control signal. Then we make numerical investigations of different shapes for the optical control signal. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: feedforward control; two-level atom; modulated optical field; feedback; pulse; ileri beslemeli kontrol; iki seviyeli atomu; modüle optik alan; geri bildirim; nabız